Potensi Daun Pacar Air (Impatiens balsamina L.) dalam Menghambat Pertumbuhan Jamur Rhizopus oryzae L. - Adfa, Morina; Ekasari, Munifilia; Avidlyandi, Avidlyandi; Supriati, Rochmah; Yudha S., Salprima (Jurnal Riset Kimia, 2021)
Pacar air (Impatiens balsamina L.) plant belongs to the Balsaminaceae family and is used as an indigenous medicine in Asia for fingernail inflammation, fractures, and rheumatism treatments. Moreover, the antipruritic, antianaphylactic, antifungal, antibacterial, and antitumor activities of some compounds, especially phenolics and quinones from this plant have been studied extensively. Therefore, this study aims to determine the antifungal activity of Pacar air leaves (Impatiens balsamina L.) methanol extract against Rhizopus oryzae L. and the IC50 value. The results showed that an increase in the concentrations of I. balsamina L. leaves methanol extract significantly raised the fungal growth. Furthermore, the extract inhibition against R. oryzae L. at various concentrations of 0.5; 0.7; 0.9; 1.1; and 1.3% w/v were 10, 21.9, 58.06, 68.06, and 79.72%, respectively, while the IC50 value was 0.896%. Hence, the presence of naphthoquinones and other secondary metabolites are responsible for its antifungal activity. Based on these results, the antifungal potential of I. balsamina L. leaves against soft-rot fungi is useful in the future.